Efficacy of controlled atmosphere treatments to manage arthropod pests of dry-cured hams - Hasan, Md. Mahbub; Aikins, Michael J.; Schilling, W.; Phillips, Thomas W. (My University, 2016)
Research here explored the use of controlled atmospheres (CA) for managing arthropod pests that infest dry-cured hams. Experiments were conducted with low oxygen (O2) achieved with low pressure under a vacuum, high carbon dioxide (CO2), and ozone (O3). Results showed that both low O2 and high CO2 levels required exposures up to 144 h to kill 100% of all stages of red-legged ham beetle, Necrobia rufipes (De Geer) (Coleoptera: Cleridae) and ham mite Tyrophagus putrescentiae (Schrank) (Sarcoptiformes: Acaridae) at 23 °C. In addition, both low O2 and high CO2 had no significant mortality against the ham beetle and ham mites at short exposures ranging from 12 to 48 h. Ham beetles were more tolerant than ham mites to an atmosphere of 75.1% CO2 and low pressure of 25 mm Hg, which imposed an atmosphere estimated at 0.9% O2. Both low O2 and high CO2 trials indicated that the egg stages of both species were more tolerant than other stages tested, but N. rufipes eggs and pupae were more susceptible than larvae and adults to high concentration ozone treatments. The results indicate that O3 has potential to control ham beetles and ham mites, particularly at ≈166 ppm in just a 24 h exposure period, but O3 is known from other work to have poor penetration ability, thus it may be more difficult to apply effectively than low O2 or high CO2. would be. CA treatment for arthropod pests of dry-cured hams show promise as components of integrated pest management programs after methyl bromide is no longer available for use. © 2016 by the authors; licensee MDPI, Basel, Switzerland.
Citation: Hasan, M. M., Aikins, M. J., Schilling, W., & Phillips, T. W. (2016). Efficacy of controlled atmosphere treatments to manage arthropod pests of dry-cured hams. Insects, 7(3). doi:10.3390/insects7030044
Keywords: Carbon Dioxide; Cheese Mite; Ham Mite; Low Oxygen; Low Pressure; Mold Mite